THE IMPLEMENTATION OF EXPERIMENTAL METHODS TO STUDENTS' CRITICAL THINKING SKILLS IN ELEMENTARY SCIENCE LEARNING: LITERATURE REVIEW - Totok Bintoro; Fahrurrozi Fahrurrozi; Yofita Sari; Uswatun Hasanah; Aldin Syahdan (Universitas Pendidikan Indonesia, 2022)
This research aims to explain how experimental methods applied in science learning in Elementary School can improve abilities. Critical thinking of students. The method used in this research is literature study research. This research uses secondary data in the form of scientific journals, research results and books and other relevant sources. Data analysis techniques include three stages: organizing, synthesize, and identifying. The results of this study show that experimental methods have stages, among others: (1) identify problems (2) search for data for problem solving (3) conduct experiments (4) test the correctness of problems (5) make conclusions that have critical relevance. Critical thinking indicators that include interpretation, analysis, evaluation, and decisions. This article discusses efforts to improve critical thinking in the learning process using experimental methods.